A mídia e o presidente: um julgamento com base na teoria da valoração - Cabral, Sara Regina Scotta (2007)
Evaluation through language is a procedure which is connected to contexts of situation and also to social rules that define the behavior of a group. Through investigations in Discourse Semantics, Martin and White (2005) argue that in some discoursive domains particular conventions of composition strongly determine the evaluative styles used by their authors. Drawn from the works of Fairclough (1995) about the journalistic discourse and orientations of Systemic Functional Grammar (HALLIDAY, 1989, 1994), this work intends to investigate, in the area of Discourse Semantics, the authorial or non-authorial linguistic manifestations of judgement, around the polemic expulsion of the journalist Larry Rohter, who had suggested the alcohol abuse of the Brazilian President. The initial hypothesis was that making any public judgement against the person of Luís Inácio Lula da Silva the authors would build them in terms of social sanctions and less as social esteem. To accomplish that, 153 news articles written by Brazilian journalists were gathered, from May 10th to June 10th, 2004, and published on the Internet, in on-line newspapers and on the Observatório da Imprensa . Its initial theme was an article published on The New York Times about the supposed Presidential alcoholic habits. After the corpus selection, the texts were divided into four blocks, related to the four moments perceived during the period. Furthermore, it was made a selection of all occurrences of judgement in relation to the president s behavior in each of the movements as authorial statements and as attributions. Finally, it was elaborated a typology of 5 judgements specially for the corpus analyzed, from the cross-chek of the Appraisal Theory (MARTIN e WHITE, 2005) and the parameters of evaluation of Bednarek (2006). After the corpus manual analysis, it was used the TextStat 1.52 computational tool to verify the data obtained. The results indicate that the five parameters found - CAPACITY, USUALITY, TENACITY, VERACITY and PROPERTY -, the authorial judgement indicates negative values of social esteem, especially USUALITY and CAPACITY, and less number of social sanctions (VERACITY and PROPERTY). As to the non-authorial judgements, it was observed more frequency of TENACITY values (social esteem) and PROPERTY (social sanction) organized in the form of direct speech, with neutral or assertive verbs, and evidences of CAPACITY and USUALITY (social esteem). From the case study, it can be concluded that article writers go beyond the voice of the correspondent, but they do not reach the voice of the commentator, because there are constraints on social sanction judgements.